Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1476-5381.1993.tb13919.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of K+ channel blockers on antinociception induced by α2‐adrenoceptor, GABAB and κ‐opioid receptor agonists

Abstract: 6 These results suggest that the opening of K+ channels is involved in the antinoceptive effect of aC and GABAB, but not ic-opioid, receptor agonists. The K+ channels opened by X2-adrenoceptor agonists seem to be ATP-dependent channels, whereas those opened by GABAB receptor agonists are not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 30 publications
2
27
1
1
Order By: Relevance
“…Potassium channels modulate the drug-induced antinociception. For example, K ATP openers potentiate morphine or tricyclic antidepressant-induced analgesia in mice, while blockers which are devoid of analgesic properties do not seem to modify significantly morphine antinociception (Ocana and Baeyens, 1993;Ocana et al, 1996;). These observations are in good agreement with the absence of analgesic effects of TEA, ChTX, and GLI as observed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels modulate the drug-induced antinociception. For example, K ATP openers potentiate morphine or tricyclic antidepressant-induced analgesia in mice, while blockers which are devoid of analgesic properties do not seem to modify significantly morphine antinociception (Ocana and Baeyens, 1993;Ocana et al, 1996;). These observations are in good agreement with the absence of analgesic effects of TEA, ChTX, and GLI as observed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that the antinociceptive effect of NE is mediated by α 2 -adrenoceptors (Howe et al 1983;Fleetwood-Walker et al 1985;Yaksh 1985). The activation of α 2 -adrenoceptors increases potassium conductance in dorsal horn neurons, which produces hyperpolarization and decreases excitability, thereby contributing to analgesia (North and Yoshimura, 1984;Ocana and Baeyens, 1993;Grudt et al, 1995). On the other hand, α 2 -adrenoceptor agonists reduce the stimulus-evoked release of substance P (Kuraishi et al, 1985;Pang and Vasko, 1986) and glutamate (Kamisaki et al, 1993;Ueda et al, 1995) in the spinal cord, thus suppressing nociceptive transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Early work indicated that K ATP may mediate the analgesic effects of morphine (Ocana et al 1990) or clonidine (Ocana et al 1993) since the antinociceptive effects of these agents could be reversed by pretreatment with glibenclamide, a selective K ATP antagonist. Recent studies indicate that glibenclamide can antagonize the antinociceptive effects of a variety of compounds such as nitric oxide and cyclic GMP in an assortment of animal models of nociception, such as those wherein hyperalgesia is produced by carrageenan or prostaglandin E 2 (PGE 2 ) (Rodrigues and Duarte 2000;Soares et al 2001;Alves and Duarte, 2002).…”
Section: Introductionmentioning
confidence: 99%